Causes and Tendency of Student Dropouts in Community Colleges in Kathmandu: A Study of Baneshwor Multiple Campus - Kafle, Rameshwor; Sigdel, Uddav (Baneshwor Campus Journal of Academia, 2025)
The trend of students dropping out is currently a global concern. This problem not only affects the progress of national development. It is certain that it will affect the stability of the entire educational institution. More than that, it also directly affects the possibility of personality development of every person within the country and internationally. This research mainly focuses on the problem of dropping out without completing their studies among the students of Baneshwor Multiple Campus of Nepal. This study aims to investigate the causes and tendencies of dropout. The study attempts to conclude using campus records along with secondary data obtained from BMC's Educational Management Information System (EMIS) and primary data collected through a structured questionnaire from a sample of 177 college leavers. The descriptive research method has been used for the research. Key findings from this study show that financial problems are the biggest reason for dropping out of college, with 24.9 percent citing inability to pay fees as the main reason for dropping out. Other important factors found that 10.7 percent dropped out due to a lack of value in pursuing higher education, and another 22.0 percent due to foreign employment. This study compares other national and international research on student dropout and attempts to highlight both similarities and specific differences. Similarly, the present study attempts to suggest targeted interventions and policy changes at both institutional and governmental levels to reduce dropout rates, improve retention, and create a more supportive learning environment.